FLEXURAL STRENGTH OF BAMBOO AND STEEL REINFORCED CONCRETE BEAM - Mbazor, Chukwu; Kaura, J. M.; Ocholi, A.; Ochepo, J.; Ibedu, K. E. (FUDMA Journal of Sciences, 2023)
There is no doubt that construction and building industries are the main energy and materials consumers of any country. In sustainable development, both the immediate and imminent needs are adequately taken into consideration. Sequel to the fact that concrete is weak in tension, reinforcement is inevitable to compensate for the deficiency. This paper purposes to comparing the flexural properties of concrete beams reinforced with bamboo strips and steel bars. Bamboo strips were found to be a close replacement to steel for light-weight constructions. This research consists of 100 x 100 x 450mm reinforced concrete beams with varying percentages of steel served as reference. Three beams were cast for each bamboo/Steel reinforcement ratio for each curing age making a total of Ninety-Six beams for flexural properties test. Three cubes were prepaid for every curing age summing up to Twenty-Four cubes for compressive test. The area of Bamboo reinforcement equivalent to steel was calculated via the equivalence of the force that could withstand the bending stresses which was also resisted by corresponding bamboo area. Steel stirrups were used to carter for shear in the beams. Flexural and compressive strengths at 7-, 14-, 21- and 28-days have been taken into consideration for comparison purpose. The graphs from the results were plotted and the suitability of bamboo reinforced beam was discoursed regarding the failure types. Results from the research reveal that bamboo can be used in low-cost constructions.
Keywords: Bamboo; Building; Concrete Beam; Construction; Equivalence; Industries; Steel; Reinforcement Area